Economic Determinants of The Development of The Historic Hotel Industry: A Case Study of Poland’s Zachodniopomorskie and Dolnośląskie Provinces - Wojciech SADKOWSKI; Krzysztof SALA (Communications of International Proceedings, 2024)
The motivation for the study stemmed from the long-standing research interests of both authors. The subject matter of the undertaken study is related to the continuation of previously conducted research on historic hotels and its extension aimed at including economic issues, as well as financial factors influencing the development of this type of hotel establishments. The authors managed to reach a representative group of managers or owners of historic hotels from two purposively selected Polish regions characterised by a distinctively significant flow of customers, including in the sector of historic hotels. To date, various research projects conducted in Poland and abroad have not addressed the issues of economic and financial factors influencing the development of historic hotels in regional arrangements. Having identified the existing research gap, the authors decided to conduct a new study of this topic, taking into account the post-pandemic situation and the impact of the war in Ukraine on the factors mentioned above. The participants of the study were a purposively selected and representative group of owners and managers of historic hotels of all categories from the Polish regions of Lower Silesia and West Pomerania, located in both urban centres and rural areas. The applied research method was a diagnostic survey using a questionnaire technique. The results of the study allowed for the identification of the following key factors determining the development of historic hotels in the two selected regions in Poland: geographical and architectural features, financial aspects, service quality and legal circumstances.
Keywords: Economic factors; Historic hotel industry; Regional arrangements; War in Ukraine